Increase of Adverse Events After Intravenous Injection of Gentamicin in Horses Between 2015 and 2017—From Marketing Authorization Holder's Point of View - Stammwitz, Viola; Honnens, Änne; Hochhuth, Dieter; Schuberth, Hans-Joachim (Frontiers in Veterinary Science, 2021)
Between 2015 and 2017 a marked increase of anaphylactic-like reactions after intravenous administration of gentamicin was seen first in horses and later also in humans. This world-wide issue led to safety measures including product recalls and safety warnings. In this article the Germany-based Marketing Authorisation Holder (MAH) of a veterinary gentamicin product that was early and intensely affected, describes how this company’s clinical approach to root cause analysis led to the discovery of the causative agent in the active pharmaceutical ingredient (API). MAH shows their own pharmacovigilance data and describes pharmacovigilance phaenomena seen during this episode. An overview is given on further investigations of the API manufacturer and measures taken by all involved parties including competent authorities to reestablish a safe use of gentamicin products. The histamine-contamination of gentamicin was an exceptional incident of global extent affecting not only veterinary but also human drug safety. The reactions in horses turned out to be an indicator for a health threat also to humans and in the end contributed to an improvement in the safety of human and veterinary medicinal products containing fermentative APIs. The extreme dimensions of this issue point out the important role veterinary clinicians and practitioners play in spontaneous reporting-based pharmacovigilance systems and by this, in drug safety.